Improving learning experience through process re-engineering: Khan Academy localization into Azerbaijani - Ayaz Karimov; Alexander Nolte; Irene-Angelica Chounta; Mirka Saarela; Tommi Kärkkäinen (Frontiers in Education)
The localization of online educational platforms brings many benefits to the students and teachers such as access to different types of textual and video content. Nonetheless, it demands time and capital resources to localize any content. The aim of this research was to re-engineer the entire localization process of Khan Academy content into the Azerbaijani language and evaluate its impact on users’ learning experience. For this purpose, we implemented process re-engineering’s cycle of successive steps. Additionally, we carried out a survey to investigate the new localization process’s effect on users’ learning experience. Our study found that making the localization process more efficient decreased the time and resources needed. Additionally, this improved process positively affected how users experienced learning on the platform.